Uji Adaptasi Beberapa Varietas Sorgum (Sorghum bicolor L.) pada Lahan Kering di Kabupaten Ciamis, Jawa Barat - Nana Sutrisna; Nandang Sunandar; Anas Zubair (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2013)
Sorghum is one of the crops that can be used as a source of food, animal feed, and industrial raw materials. Sorghum is also resistant to drought, so the potential to be developed on land suboptimal, including on dry land in Kudat District, West Java Province. The research aims to determine the adaptability of some varieties of sorghum on dry land in Kudat District, West Java Province. Research conducted dilahan farmers in July to November 2011. Experiments using Randomized Complete (RAKL) with seven varieties of treatment and repeated three times. To seven varieties tested were (1) Numbu, (2) Kawali, (3), Padjadjaran University 1, (4) Padjadjaran 2, (5) Batari, (6) Keller, and (7) Taomitsu. Data growth and yield components and yield is analyzed by the Duncan test at 5% level. The results showed that (a) all of the tested sorghum varieties well-adapted to dry land in Kudat District, West Java Province, and (2) varieties numbu, unpad 2, and Kawali give different results, both to the growth variables and components yield and productivity but better than the four other varieties, so that the three varieties can be developed on dry land in Kudat District, West Java Province.